Witnessing stories in the Grey Zone: complicity and anthropological research in Mozambique - Carvalho, X. (Complicity Conference, Understanding Conflict research cluster, College of Arts and Humanities, University of Brighton, 2015)
At the beginning of the year 2012 I was returning home in Maputo, the capital city ofMozambique in Southern Africa. As I was arriving home, a group of people startedchasing a young boy. The group consisted of more or less 20 people, local neighbors.Among them were women and men, boys and girls. They all ran after the young boy, screaming and threatening him, shouting “agarra Moluene, agarra Moluene” (meaning: “grab the street children ”). After a while, they grabbed him and started to beat him up.I stayed there as a witness for a short time. Then I left. Did the young boy die? Almost.Did I have the moral duty to intervene? I will argue that when conducting ethnographicfieldwork the central issue is in the relationship between the anthropologist and theparticipants, in which complicity plays a central role (Marcus 1997, 1986; Geertz 1986;Clifford 1986). This relationship is complex and most of the times occurs in the grey zone, a concept developed by Primo Levi (1986) about his experience as a survivor ofAuschwitz, the Nazi extermination camp. The grey zone is a metaphor for moral ambiguity when living under extreme and co-coercive situations in which there is nogood or evil, right or wrong, friends or enemies. However an understanding of the grey zone is also interconnected with the role of the anthropologist as a witness duringfieldwork, particularly when dealing with the imbalances of power in the uncovering ofproblems and the possibilities of being able to solve them, resulting in a moral tensionbetween the anthropologist and the participants (Geertz 1968).